Dual Frequency Continuous Wave Radar for Small Displacement Detection - Andarining Palupi; Aloysius Adya Pramudita; Dharu Arseno; Antonius Darma Setiawan (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
In several field such as structure health monitoring, landslide monitoring and medical measurement, small displacement is used as the indicator of any problem that may rise in such fields. High resolution radar system is required for small displacement detection in millimeter of centimeter scale. Continuous wave (CW) radar with its narrow bandwidth feature, has a simpler system comparing with other radar system. However, the modification is needed to present the ability of CW radar in detecting small displacement. In this paper, dual frequency CW radar was investigated and proposed for small displacement detection. Computer simulation has been conducted to study the capability of the proposed radar system. The result shows that the dual frequency CW radar at 10.525 GHz is capable to detect a small displacement in millimeter scale. The frequency difference of the radar signal needs to be adjusted to avoid the ambiguity in the detection result